Wind-interference effect on an octagonal building in varying positions by large eddy simulation. Issue 1 (January 2022) - Kar, Rony; Dalui, Sujit K
Three square plan shaped tall buildings are arranged at the vertices of an equilateral triangle of varying size. The octagonal plan shaped principal building is also positioned randomly such that the position of the principal building is never overlapped with the square plan shaped buildings. The effect of interference of the square buildings on the wind-induced responses of the principal building is thoroughly measured by computational fluid dynamics using large eddy simulation turbulence model. Metamodels for drag and lift coefficients of the principal building in the interfering conditions are established. Interference factors for the pressure coefficients at different faces of the principal building is calculated and cast into efficient mathematical models. Pareto optimality for the maximum interference criterion is obtained. The optimal positions of the principal and interfering buildings for maximum interference are plotted. Selected cases from the Pareto optima are analysed to obtain the transient wind effects for those interference cases. The peak and root-mean-square pressure coefficients of these interfering conditions are compared with that of the isolated condition. The difference between the power spectra of the isolated and interfering conditions are also depicted.